Systematic Trials of Lac Cultivation on Ghont (Ziziphus xylopprus Willd.) in Madhya Pradesh-requirement of Broodlac for Crop Inoculation - Mehra, B. P.; Gokulpure, R. S.; Sah, B. N. (Indian Forester, 1971)
Quantities of broodlac to be used on ghoni for crop inoculation of Baisakhi and Katki have been determined. About 270 gm broodlac may be used for Baisakhi crop inoculation and 530 gm per tree for Katki crop inoculation. Heavy inoculation yields a poor Baisakhi crop but satisfactory Katki crop.